Pengaruh Komunikasi, Pengembangan Karir, Dan Etos Kerja Terhadap Kinerja Karyawan Pada Ksp Kopdit Hiro Heling - Yulfianti Dua Ose; Yosefina Andia Dekratia; Magdalena Samosir (Universitas Nusa Nipa Maumere, 2023)
This research aimed to: (1) find out the description of employee performance, communication, career development, and work ethic and (2) analyze the effect of communication, career development, and work ethic on employee performance both partially and simultaneously.The populations in this research were Hiro Heling Credit Union employees as many as 63 people. This research was done by census or saturated sampling due limited population. Data were collected through questionnaires and analyzed through descriptive and inferential statistical methods, namely multiple linear regression. Hypothesis testing was done through the F-test and t-test.The results of descriptive analysis showed that the variables of employee performance, communication, and career development were categorized as good enough while work ethic was categorized as good. The statistical result of the t-test showed that partially, the variables of communication, career development, and work ethic had a positive and significant influence on employee performance. The statistical results of the F-test showed that simultaneously, all independent variables had a significant influence on employee performance. The results of the determination analysis indicated that three independent variables in this research could explain the fluctuating performance of employees at Hiro Heling Credit Union by 47,4%.